Analysis of spatiotemporal evolution characteristics and driving factors of carbon storage in Dongting Lake Wetland, China - Nian-qing Zhou; Ke-hao Liu; Meng-shen Guo; Yi Cai; Zai-ai Wang; Wen-gang Zhao (Journal of Groundwater Science and Engineering)
Lake wetlands play a crucial role as global carbon sinks, significantly contributing to carbon storage and ecological balance. This study estimates the quarterly carbon storage in the Dongting Lake wetland for the years 2010, 2015, and 2020, using MODIS remote sensing imagery and the InVEST model. A Structural Equation Model (SEM) was then employed to analyze the driving factors behind changes in carbon storage. Results show that intra-annual carbon storage increases and then decreases, with maximum level in the third quarter (average of 34.242 Tg) and a minimum one in the first quarter (average of 21.435 Tg). From 2010 to 2020, inter-annual carbon storage variations initially exhibited an increasing trend before decreasing, with the peak annual average carbon storage reaching 32.230 Tg in 2015. Notably, the coefficient of variation for intra-annual carbon storage increased from 8.5% in 2010 to 25.8% in 2020. Key driving factors that influence carbon storage changes include surface solar radiation, temperature, and water level, with carbon storage positively correlated with surface solar radiation and temperature, and negatively correlated with water level. These findings reveal the spatiotemporal evolution characteristics of carbon storage in the Dongting Lake wetland, offering scientific guidance for wetland conservation and regional climate adaptation policies.